2018
DOI: 10.1088/1361-6463/aadfad
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of discharge with liquid non-metallic cathode burning in air flow

Abstract: Conference papers Accès au bibtex titre Calcul de la composition chimique dans un plasma issu de mélanges de PTFE, d'air, de cuivre et de vapeur d'eau dans le cadre d'appareillages de coupure électrique à air

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
8
0
1
Order By: Relevance
“…Low-current discharges in atmospheric-pressure air have been studied in a number of experiments (see recent reviews [32][33][34] and references therein). In most of the experiments, for which current density values j are available [3,[35][36][37][38][39][40][41][42][43][44][45], the current discharge radius was inferred by the emission spectroscopy of the N 2 C state. However, the emission discharge and the current discharge radii may be not equal, and both their radii and their ratios depend on experimental conditions [5,46].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Low-current discharges in atmospheric-pressure air have been studied in a number of experiments (see recent reviews [32][33][34] and references therein). In most of the experiments, for which current density values j are available [3,[35][36][37][38][39][40][41][42][43][44][45], the current discharge radius was inferred by the emission spectroscopy of the N 2 C state. However, the emission discharge and the current discharge radii may be not equal, and both their radii and their ratios depend on experimental conditions [5,46].…”
Section: Resultsmentioning
confidence: 99%
“…However, the emission discharge and the current discharge radii may be not equal, and both their radii and their ratios depend on experimental conditions [5,46]. As a result, variation of cathode materials (e.g., glow discharges with liquid [35,40,41], plasma [36,37], or metal [3,38,39,[42][43][44][45] cathodes), stabilization modes (with or without tubes and flows as well as swirl versus axial flows [38]), or the electrode gaps and of discharge currents causes a large scatter of discharge parameter data in terms of the current density. In any case, since the C state of N 2 is produced by electron-impact excitation, the available current density values are representative of regions with high electron number density.…”
Section: Resultsmentioning
confidence: 99%
“…The requirement for special gases and problems with scaling render treatment costly and limit conventional NEAPPJs to laboratory studies and research applications. Considering the high price of process gases, the perfect solution would be the development of a high-density plasma jet operated with the flow of natural air; however, the generation of high density and low temperature plasma in ambient air remains challenging [22], [24], [28]- [30]. Several studies reported the development of plasma jets operated with natural air; however, in all the reports, the plasma jets encountered the problems that were discussed above (complex gas flow, low concentrations of RONS, and problems with scaling) and relatively high plasma temperature, thereby resulting in thermal damage to the device [29], [31].…”
Section: Introductionmentioning
confidence: 99%
“…A number of experiments have been reported on non-equilibrium regimes of discharges in atmospheric-pressure air, in particular, glow-type discharges in open ambient air (e.g., [1,2,3,4,5,6,7,8,9,10,11,12]), and in fast longitudinal flows of air [13,14]. In [13,14], the parameters of a low-current glow discharge in a high-velocity flow of preliminary heated air ( T 0 = 1800–2900 K) at atmospheric pressure, is investigated.…”
Section: Introductionmentioning
confidence: 99%